Where will grandma live: an intergenerational housing review - Wise, Courtney Nicole (Kansas State University, 2024)
Some seniors have the resources and the ability to choose where they want to live, others live on limited income and struggle to find housing that meets their needs. This is why it should be a priority to build places of quality that offer them a community. This study employs a single case study approach to discover what barriers and opportunities are present in creating a multigenerational living community. Information gathered from this case study research can then be used by others interested in creating a community of their own, who seek guidance with the process. The implication is that if more people create communities with a focus of interaction between generations, then seniors’ quality of life will increase.
Keywords: Inclusionary planning; Senior housing; Multigenerational; Low-income senior housing